Primary Care Providers' Communication About Medical Cannabis With Older Adults: A Cross-Sectional Survey - Abdallah W. Elbready; Ilene Warner-Maron; Allen Glicksman; Andrew M. Peterson (SAGE Publishing, 2024)
Purpose: Healthcare providers often hesitate to discuss medical cannabis (MC) due to limited understanding, risks and benefits, and misinformation. This reluctance is notable with older adult patients, despite MC's potential benefits. This study investigates whether primary care providers (PCPs) routinely inquire about MC when treating older adults and the frequency of such inquiries. Methods: A 23-question survey was emailed to 575 physicians, pharmacists, nurse practitioners, and physician assistants who completed a Pennsylvania Department of Health-approved MC course. The survey was conducted in 2022 to 2023, and the participants were drawn from a pool of individuals who completed the course between 2018 and 2022. PCPs need to be practicing in the Tri-state area and caring for older adults. Results were cross-tabulated to examine the relationship between healthcare practitioners' inquiries about MC and patients' questions about MC. McNemar and Chi-square tests were used for analysis. Results: Survey results revealed that PCPs were more likely to inquire about alcohol and tobacco use than cannabis with older adults ( P  < .0001). Patients were more likely to initiate conversations about MC use ( P  = .037). PCPs did not frequently inquire about cannabis use amongst their patients or consider it as a therapeutic option. Conclusion: This study underscores the prevalent reluctance among PCPs to initiate discussions about MC treatment with older adults. Further investigation is needed to identify how to improve communication regarding the risks and benefits of MC.